ADDRESSING AUDITING CHALLENGES THROUGH EMERGING TECHNOLOGIES A CASE STUDY OF CROWE AL MUHANNA & CO - Rejoy, Alan Varghese; Satsangi, Priya; Padroo, Bhawna Sharma (International Journal of Research -GRANTHAALAYAH, 2025)
The auditing profession is undergoing a significant transformation driven by technological advancements, increasing regulatory expectations, and the growing complexity of financial reporting. Traditional auditing practices, which depend heavily on manual procedures such as trial balance preparation, ledger reconciliation, and year-over-year analysis, are proving inadequate in today’s data-intensive environment. This research paper examines how emerging technologies including Artificial Intelligence (AI), Business Intelligence (BI), Robotic Process Automation (RPA), and automated Trial Balance extraction tools can address these challenges. Using a qualitative case study based on the internship experience at Crowe Al Muhanna & Co., combined with benchmarking insights from Deloitte’s digital audit tools, the study demonstrates how automation improves efficiency, reduces human error, enhances analytical depth, and strengthens the overall quality of audits. While the adoption of such technologies presents challenges related to training, financial investment, and data governance, the findings show that these technological tools represent a substantial opportunity for mid-sized audit firms to modernize and align with global standards. The study concludes with practical recommendations for future technology adoption, positioning the paper for academic publication in commerce and management journals.